2020
DOI: 10.3389/fonc.2020.00861
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience of the First Single-Room Gantry Mounted Active Scanning Proton Therapy System at an Integrated Cancer Center

Abstract: Introduction: Review the early experience with a single-room gantry mounted active scanning proton therapy system. Material and Methods: All patients treated with proton beam radiotherapy (PBT) were enrolled in an institutional review board-approved patient registry. Proton beam radiotherapy was delivered with a 250 MeV gantry mounted synchrocyclotron in a single-room integrated facility within the pre-existing cancer center. Demographic data, cancer diagnoses, treatment technique, and geographic patterns were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Surprisingly, there is a paucity of data about downtime of PT and MRL machines. For PT it is reported that downtime more frequently leads to delayed than to missed treatments; others report to replace PT by photon fractions [19][20], which is probably dependent on whether photon therapy is available on site, and on the indication for which PT was given. Switching to photon therapy may appear problematic for a patient, but may be preferred for tumours for which a treatment interruption is associated with impaired local tumour control rates.…”
Section: Intervention Source and Design Quality: Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, there is a paucity of data about downtime of PT and MRL machines. For PT it is reported that downtime more frequently leads to delayed than to missed treatments; others report to replace PT by photon fractions [19][20], which is probably dependent on whether photon therapy is available on site, and on the indication for which PT was given. Switching to photon therapy may appear problematic for a patient, but may be preferred for tumours for which a treatment interruption is associated with impaired local tumour control rates.…”
Section: Intervention Source and Design Quality: Technologymentioning
confidence: 99%
“…Ó 2021 The Authors. Published by Elsevier B.V. Radiotherapy and Oncology 167 (2022) [14][15][16][17][18][19][20][21][22][23][24] This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).…”
Section: Introductionmentioning
confidence: 99%
“…Proposals over the past several years have suggested movement to a single model of reimbursement agnostic of therapy approach, implying that proton and photon case reimbursement including the use of advanced technologies would be identical. Although these models for reimbursement have not yet been implemented, institutions planning on developing proton care must remain cognizant that reimbursement models will likely change in the near future and a strategy for both growth and cost containment must be incorporated into the business plan for proton development moving forward [25,26].…”
Section: Financial Considerationsmentioning
confidence: 99%
“…The goal for proton care moving forward is to integrate to advantages of photon care into the proton footprint. This would include tools for image guidance, beam precision, and optical tracking as well as create synergy and integration among the physics and therapy staff [25,26].…”
Section: Adjustments In Proton Footprint For Future Carementioning
confidence: 99%
See 1 more Smart Citation